Improvement of 2-μm Thulium-Doped Fiber Lasers via ASE Suppression Using All-Solid Low-Pass Photonic Bandgap Fibers - Kakaie, Zahra; Sharbirin, Anir Syazwan; Mahdiraji, Ghafour Amouzad; Adikan, Faisal Rafiq Mahamd; Ismail, Mohammad Faizal; Ahmad, Harith (Institute of Electrical and Electronics Engineers, 2019)
All-solid photonic bandgap fibers (PBGFs) were designed and fabricated to work as low-pass filters in 2-μm region. They were used for manipulating thulium doped fiber laser (TDFL) operating in the 2-μm region via amplified spontaneous emission suppression. A sharp lasing peak at 1915 nm was achieved using a single-stage TDFL with full width at half maximum and optical signal-to-noise ratio of 0.3 nm and 39.5 dB, respectively. This lasing is achieved using the fabricated PBGF low-pass filter with cutoff wavelength at 1945 μm and loss of more than 25 dB. In this respect, the resultant TDFL performed better than the one that did not employ the low-pass filter. In this paper, we present a few representative cases involving the all-solid PBGF. We have shown that by increasing the diameter of the fabricated PBGF from 142 to 189 μm, their cutoffs related to their bandgaps shifted from 1727 nm toward longer wavelengths, 2079 nm. As a result, lasers with different wavelengths were generated within 2-μm region. © 1983-2012 IEEE.